2000
DOI: 10.1126/science.288.5470.1402
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of Adsorbate Atom Motion Above a Metal Surface

Abstract: The dynamics of cesium atom motion above the copper(111) surface following electronic excitation with light was studied with femtosecond (10(-15) seconds) time resolution. Unusual changes in the surface electronic structure within 160 femtoseconds after excitation, observed by time-resolved two-photon photoemission spectroscopy, are attributed to atomic motion in a copper-cesium bond-breaking process. Describing the change in energy of the cesium antibonding state with a simple classical model provides informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
226
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(235 citation statements)
references
References 21 publications
7
226
1
1
Order By: Relevance
“…1). The inelastic channel gives similar contributions in both cases leading to values of lifetimes that are in reasonable agreement with the experimental values [281][282][283][284]287]. A theoretical study, together with a comparison of the available experimental data, of the lifetime of electronically excited states in the Na, K, Rb, Cs/Cu(1 1 1) systems has been made by Borisov et al [328].…”
Section: Adsorbate States: Alkali Metalssupporting
confidence: 56%
See 1 more Smart Citation
“…1). The inelastic channel gives similar contributions in both cases leading to values of lifetimes that are in reasonable agreement with the experimental values [281][282][283][284]287]. A theoretical study, together with a comparison of the available experimental data, of the lifetime of electronically excited states in the Na, K, Rb, Cs/Cu(1 1 1) systems has been made by Borisov et al [328].…”
Section: Adsorbate States: Alkali Metalssupporting
confidence: 56%
“…Due to the long time it takes for the excitation to delocalize [286], the beginning of desorption could be monitored for this system. It manifests itself in a time-dependent shift of the energy of the 6s-derived state and a non-exponential decay [287,288].…”
Section: Adsorbate Statesmentioning
confidence: 99%
“…12,13 More specifically, the dynamical behavior of nonequilibrium electrons (NEs) governs the yield of hot electron-mediated surface reactions on metal surfaces. [14][15][16] The hot electron cooling dynamics 17 as well as the mechanism of breathing modes excitation 18 has already been reported for gold NPs. At present, the internal thermalization dynamics has been mainly investigated in bulk metals [19][20][21] and naked metal nanoparticles.…”
mentioning
confidence: 99%
“…[40][41][42] A long decay time is relevant for physical processes exploiting the alkali resonance as transient state, for example, increasing the efficiency of photo-induced desorption processes. 62,63 Angleand time-resolved photoemission experiments (AR-2PPE, TR-2PPE) characterized also a second resonance, at higher energies with respect to the σ one, which displays a maximum in intensity off-normal and has been thus identified as a π resonance (m = 1). 64 For what concerns the theoretical studies, different approaches can be found in the literature.…”
Section: Resultsmentioning
confidence: 99%